استراتيجية تفكيك ابجدية ضوء الأسماء الأولى ولسانها للشاعر شاكر مجيد سيفو - خليف خضير الحياني, محمود; محمد طيب, ريم (Journal of College of Education, 2019)
The game of demolition and construction manifests itself in an attempt to dismantle and undermine the organic relationship between writing and sound. The game practiced by language is a game of temptation, paradox, presence and permanent absence. T or all of the significance tried to undermine and Deconstruction demolished, rebuilt on new foundations provide Baguaah and evasive; therefore the holiness of the name, character, and their lights, and cussing in the creative texts of Shaker Majid Sipho will exercise strategy Deconstruction undermining.
Keywords: strategy ، Disassembly ، the difference ، The effect ، the sound